If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2m + -4.9 = -3.6 Reorder the terms: -4.9 + 2m = -3.6 Solving -4.9 + 2m = -3.6 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '4.9' to each side of the equation. -4.9 + 4.9 + 2m = -3.6 + 4.9 Combine like terms: -4.9 + 4.9 = 0.0 0.0 + 2m = -3.6 + 4.9 2m = -3.6 + 4.9 Combine like terms: -3.6 + 4.9 = 1.3 2m = 1.3 Divide each side by '2'. m = 0.65 Simplifying m = 0.65
| 3(55+15)=180 | | 3x+3.3y=-2.4 | | 15-3x=10x+45 | | 3/8*x=3/40 | | x+3t+-7=29 | | 13x^2-52x=0 | | 1/2*9/4*x=9/8 | | 13x+8=47 | | m=368mm | | 7pq^2-5pq(2-q)= | | 7/2*x=63/4 | | 3x^3+16=0 | | 3a^2-13a-10=0 | | 4a-5+4g+6=12 | | 2/3*9=x | | 4x+7=5x-18 | | 0.5(x-12)=24 | | a+2=a+3-1-1 | | a+2=a+3-1 | | a+2=a+3 | | 8+3m=7 | | 34y+16=84 | | 2/5*x=7/15 | | .76+.16t=1.48t-1 | | 8y=16x-24 | | -7n+17=-6n-8 | | 7x+10=6x+11 | | 12-(5x)=52 | | 8(x+7)-2=54 | | 4x+6+3x+9+8x-3=180 | | 24m+3=27 | | x^2-16x-26=7x-4 |